Structural and magnetic studies of Ce-Zn doped M-type SrFe12O19 hexagonal ferrite synthesized by sol-gel auto-combustion method. Issue 1 (January 2019) - Yasmin, Nazia; Iqbal, Muhammad Zubair; Zahid, Maria; Gillani, Saher Fatima; Ashiq, Muhammad Naeem; Inam, Iqra; Abdulsatar, Sidra; Safdar, Muhammad; Mirza, Misbah
Abstract: In the present work, the M-type Sr-hexagonal ferrites having chemical composition Sr1-x Cex Fe12-y Zny O19 (x = 0.000, 0.025, 0.050, 0.075, 0.10, y = 0.00, 0.25, 0.50, 0.75, 1.0) are prepared via sol-gel autocombustion technique. The Structural and magnetic properties of M-type Sr-hexagonal ferrites are studied and discussed thoroughly. The structural, micro graphical and magnetic particularities of the samples are calculated through X-Ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM) respectively. X-ray diffraction assured that all the synthesized composites possess a pure M-type hexaferrite structure and basic crystalline configuration of Sr-hexaferrite which does not alter by Ce-Zn substitution. It is observed that the Ce-Zn substitution has significant effect on its magnetic properties. VSM results reveal that pure sample has coercivity of 4.49 kOe, which shows the hard nature of the samples. It is perceived that values of remanence (Mr ) and saturation magnetization (Ms ) decline with increasing the Ce-Zn ions substitution. The reason behind the reduction in magnetic saturation (Ms ) and remanence (Mr ) might be spin canting and dilution phenomena with increasing the rare earth substituted ions. The large coercivity magnets may be valuable for permanent (stable) magnet applications. The prepared composites could be useful for applications in microwave absorbing materials.